2009
DOI: 10.1073/pnas.0812719106
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer in the Rhodobacter sphaeroides reaction center assembled with zinc bacteriochlorophyll

Abstract: The cofactor composition and electron-transfer kinetics of the reaction center (RC) from a magnesium chelatase (bchD) mutant of Rhodobacter sphaeroides were characterized. In this RC, the special pair (P) and accessory (B) bacteriochlorophyll (BChl) -binding sites contain Zn-BChl rather than BChl a. Spectroscopic measurements reveal that Zn-BChl also occupies the H sites that are normally occupied by bacteriopheophytin in wild type, and at least 1 of these Zn-BChl molecules is involved in electron transfer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…Recent results on the reaction center containing Zn-BChl from a magnesium chelatase-deleted mutant of Rhodobacter sphaeroides indicated that Zn-BChl occupied the BPhe site and was involved in the electron transfer. 44 This unique feature might originate from difference in demetalation properties between Mg-BChl and Zn-BChl, namely, Zn-BChl was more tolerant to demetalation than Mg-BChl. 35 In contrast, Acidiphilium rubrum, containing Zn-BChl as a major photosynthetic pigment, which grows under acidic conditions, possesses BPhe, not Zn-BChl, in the site of the electron acceptor in the reaction center.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results on the reaction center containing Zn-BChl from a magnesium chelatase-deleted mutant of Rhodobacter sphaeroides indicated that Zn-BChl occupied the BPhe site and was involved in the electron transfer. 44 This unique feature might originate from difference in demetalation properties between Mg-BChl and Zn-BChl, namely, Zn-BChl was more tolerant to demetalation than Mg-BChl. 35 In contrast, Acidiphilium rubrum, containing Zn-BChl as a major photosynthetic pigment, which grows under acidic conditions, possesses BPhe, not Zn-BChl, in the site of the electron acceptor in the reaction center.…”
Section: Discussionmentioning
confidence: 99%
“…But many research groups turned to picosecond spectroscopy because the field seemed promising and more open. Among the contributors, I wish to mention Jean-Louis Martin, with Jacques Breton and Marten Vos, at ENSTA; Vlad Shuvalov in Puschino; Rienk van Grondelle in Amsterdam; Dewey Holten in St Louis; Maurice Windsor in Pullman; Alfred Holzwarth in Mülheim; Jim Allen and Neal Woodbury in Tempe, and others [32][33][34][35][36][37][38][39].…”
Section: Flash Absorption Spectroscopy Started In 1949 (By Pm)mentioning
confidence: 99%
“…Attenuated electron transfer rates may be caused by the presence of a molecular blocking layer because the distance between HQ and electrode is increased or the increased surface coverage on the electrode surface decreases surface accessibility for redox species, for example. Under these conditions in PBS pH 7.2 the first electron transfer of HQ is favorable in reducing P + , which has a midpoint potential of approximately 0.5 V. [29] The coverage of the molecular blocking layer on the gold electrode was estimated using cyclic voltammetry (CV) measured in the dark. On an unmodified bare gold surface, the presence of 10 mM HQ resulted in reversible reductive and oxidative peaks at 0.2 and 0.36 V, respectively, corresponding to the first of the two-electron step redox reaction of HQ with an approximate reductive midpoint potential of E m,1 = 0.28 V. The midpoint potential of the second of the two-electron step redox reaction was estimated at E m,2 = 0.54 V, with reductive and oxidative peaks at 0.54 and 0.6 V, respectively (Figure 2, red).…”
Section: Characterization Of the Molecular-modified Electrode Surfacementioning
confidence: 99%
“…On an unmodified bare gold surface, the presence of 10 mM HQ resulted in reversible reductive and oxidative peaks at 0.2 and 0.36 V, respectively, corresponding to the first of the two-electron step redox reaction of HQ with an approximate reductive midpoint potential of E m,1 = 0.28 V. The midpoint potential of the second of the two-electron step redox reaction was estimated at E m,2 = 0.54 V, with reductive and oxidative peaks at 0.54 and 0.6 V, respectively (Figure 2, red). Under these conditions in PBS pH 7.2 the first electron transfer of HQ is favorable in reducing P + , which has a midpoint potential of approximately 0.5 V. [29] The coverage of the molecular blocking layer on the gold electrode was estimated using cyclic voltammetry (CV) measured in the dark. The immersion of a freshly prepared clean gold electrode into a solution of mercaptohexanol (MCH) resulted in the formation of a self-assembled alkylthiol monolayer (SAM), which led to a decrease in interfacial capacitance and significantly impeded electron transfer, resulting in attenuated HQ redox peaks A) The spatial arrangement of redox-active cofactors in the wild type RC.…”
Section: Characterization Of the Molecular-modified Electrode Surfacementioning
confidence: 99%